Assessing the Therapeutic Outcomes and Safety Profile of Topical Steroids in Pediatric Atopic Dermatitis: A Cohort Study - Zahid, Hira; Nazar, Zaeem; Hussain, Asma; Bano, Asma; Perveen, Zahida; Jabbar, Asjid (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the efficacy and safety of topical corticosteroids in treating pediatric patients with atopic dermatitis (AD) in Pakistan, and to determine the optimal treatment regimen based on patient response. Methods: This prospective cohort study was conducted at Jinnah Hospital, a tertiary care hospital in Lahore, Pakistan, over a period of 12 months. A total of 150 pediatric patients, aged 1–12 years, diagnosed with moderate-to-severe atopic dermatitis were enrolled. Participants were treated with different strengths of topical corticosteroids (mild, moderate, and potent) based on the severity of their condition. Treatment efficacy was assessed by the reduction in the Eczema Area and Severity Index (EASI) score and clinical improvement, while safety was monitored through the occurrence of side effects, such as skin thinning, striae, and delayed wound healing. Follow-up visits were scheduled at 2, 4, and 8 weeks, with data collection at each visit. Results:Of the 150 enrolled patients, 140 completed the study. The mean age of participants was 6.2 ± 3.1 years, with 60% being male. After 8 weeks of treatment, 85% of patients showed significant improvement in their EASI scores, with a 70% reduction in overall severity. In the group using mild corticosteroids, 75% of patients showed improvement, whereas 90% of patients using moderate to potent corticosteroids experienced better outcomes. However, 15% of patients using moderate to potent corticosteroids developed mild side effects such as skin thinning and delayed wound healing, which resolved upon discontinuation of therapy. No severe side effects, including adrenal suppression or growth retardation, were observed. Conclusion:Topical corticosteroids are an effective treatment for pediatric atopic dermatitis in Pakistan, with moderate to potent steroids showing the best clinical outcomes. However, close monitoring for side effects is essential, particularly in patients requiring higher-potency steroids. Further studies with a larger sample size and long-term follow-up are recommended to confirm these findings and determine the long-term safety of corticosteroid use in children..